The primate fossil record in the Iberian Peninsula - Marigó, J.; Susanna, I.; Minwer-Barakat, R.; Madurell-Malapeira, J.; Moyà-Solà, S.; Casanovas-Vilar, I.; Robles, J.M.; Alba, D.M. (Journal of Iberian Geology, 2014)
During the last decade, new discoveries in several Iberian basins, together with the description of previously unpublished finds, have significantly increased the recorded paleodiversity of fossil Primates (Mammalia: Euarchonta) in the Iberian Peninsula. Here we provide an updated compendium of the primate fossil record in Iberia during the Cenozoic and further summarize the changes in primate paleodiversity through time, which are then analyzed in the light of changing climatic conditions. Thanks to favorable climatic conditions, the highest diversity of Iberian primates was reached during the Eocene, thus reflecting the radiation of both adapoids and omomyoids; only a single plesiadapiform genus is in contrast recorded in the Iberian Peninsula. Near the Eocene-Oligocene boundary, paleoclimatic changes led to a primate diversity crisis and other faunal changes, although two Iberian omomyoids survived the Grande Coupure. From the Middle Miocene onwards, catarrhine primates are recorded in the Iberian Peninsula. During the Middle and Late Miocene, they are represented by pliopithecoids and hominoids, restricted to NE Iberia. The Miocene hominoids from Iberia are of utmost significance for understanding the Eurasian hominoid radiation and its role in the origins of the great-ape-and-human clade. Following the local extinction of these taxa during the early Late Miocene, due to progressively increased seasonality and concomitant changes in plant communities, cercopithecoids are also recorded in the Iberian Peninsula from the latest Miocene through the Plio-Pleistocene, although they finally became locally extinct, whereas hominoids are again represented by fossil humans during the Pleistocene.